Validation of System Dynamics Models – a Case Study - Justyna Lemke; Małgorzata Łatuszyńska (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The purpose of this article is the analysis of the system dynamics model validation illustrated by the example of a model of the manufacturing resource allocation. In the first part of the article the authors present an overview of the definitions of validation and verification that can be found in the reference literature. Also, they emphasize the role which validation and verification play in the modeling process. Furthermore, they discuss the techniques of system dynamics model validation with particular focus on tests of the model structure, behavior and policy implications. The second part of the article contains an example of the validation process of a system dynamics model simulating manufacturing resource allocation in an electronic company. The purpose of the model is to assess the long-term effect of assigning workers to individual tasks on such production process parameters as efficiency or effective work time. The authors focus their particular attention on that part of the model which deals with a storehouse, one of the company production units. They conduct tests of its structure and behavior. When validating the structure the authors make use of the information obtained in a series of interviews with the company staff. They also refer to the generally accepted knowledge found in the reference literature. The results generated by the model in the course of the behavior tests are compared with the real data. The authors evaluate both the logic of the system behavior and the level of accuracy of the output data in reference to the real system.